96 - PILATES' METHOD THEORETICAL FUNDAMENTS: A SYSTEMATIZED REVIEW (Fiep Bulletin - online, 2011)
Abstract: Pilates' method is a physical and mental conditioning modality that dates back to the beginning og the 20th century. It has been promoted in current society as a modality able to provide balance between body, mind, physical skill, postural control and life quality. This study is a systematized review about the history, technique, practice and benefits of Pilates' exercises. Our objective is to contextualize the practice in the components of human corporeity, to contribute to the scientific knowledge about the method and add potential to it. We made us of articles recently published in databanks Scielo, Medline, Lilacs and Pubmed. In spite of well known shortage of researches in this specific area, most of the results highlight the enhancement of physical skills, postural control and contribution to rehabilitation.
Keywords: review literature as topic; exercise movement techniques / methods; history